2005
DOI: 10.1016/j.cardiores.2004.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of sarcolipin decreases myocyte contractility and calcium transient

Abstract: We conclude that SLN may play an important role in regulating the SR calcium ATPase pump, possibly by interacting with phospholamban.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 30 publications
(58 reference statements)
5
57
1
Order By: Relevance
“…These changes were associated with increased expression of SERCA2a but not PLN, suggesting that SERCA2a elevations are responsible for the enhanced Ca 2ϩ cycling and contractility in D2-overexpressing mice. However, D2 overexpression also reduced the levels of SLN, which can impair cardiac contractility and depress Ca 2ϩ cycling (26,32) in mouse myocardium as a result of either direct SERCA inhibition or synergistic interaction with PLN to form highly stable ternary SLN͞PLN͞ SERCA2a complexes (24,25). Depressed SLN levels in D2-overexpressing hearts appeared to be TH-dependent, because SLN expression was decreased in hyperthyroid hearts and increased in hypothyroid hearts.…”
Section: Effects Of D2 Expression On Cardiac Function and Ca 2؉ Cyclingmentioning
confidence: 98%
“…These changes were associated with increased expression of SERCA2a but not PLN, suggesting that SERCA2a elevations are responsible for the enhanced Ca 2ϩ cycling and contractility in D2-overexpressing mice. However, D2 overexpression also reduced the levels of SLN, which can impair cardiac contractility and depress Ca 2ϩ cycling (26,32) in mouse myocardium as a result of either direct SERCA inhibition or synergistic interaction with PLN to form highly stable ternary SLN͞PLN͞ SERCA2a complexes (24,25). Depressed SLN levels in D2-overexpressing hearts appeared to be TH-dependent, because SLN expression was decreased in hyperthyroid hearts and increased in hypothyroid hearts.…”
Section: Effects Of D2 Expression On Cardiac Function and Ca 2؉ Cyclingmentioning
confidence: 98%
“…The cytoplasmic domain IA, consisting of residues 1-20, of which the first 16 are likely in an α-helical conformation, cytoplasmic domain IB consisting of residues 21-30 and domain II with residues 31-52 is the hydrophobic transmembrane domain which is probably in an α-helical conformation [13,27,81]. On the other hand, SLN is a 31 amino acid SR membrane protein and shows a distribution pattern similar to SERCA2a and PLB [12,16]. Similar to PLB, the amino acids in SLN are organized into three domains; cytoplasmic domain, transmembrane and lumenal domains.…”
Section: Sarcolipin Is Structurally Similar To Plbmentioning
confidence: 99%
“…On the other hand, SLN levels are predominant in the atria than the ventricle [14][15][16]25]. PLB is also expressed at low levels in slow-twitch skeletal muscles [27,28].…”
Section: Sln and Plb Are Differentially Expressed During Development mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, however, the role of SLN in cardiac physiology was investigated using transgenic mouse models (11,12). Specifically, it was found that the overexpression of SLN affects calcium transport on the sarco(endo)plasmic reticulum, decreasing the amplitude of the calcium transient and the rate of muscle relaxation (11).…”
mentioning
confidence: 99%